Peran Fintech dalam Mendorong Ekonomi Inklusif Pada Usaha Mikro Wonder Craft Pesawaran - Fitri, Annisa; Farhani, Armachika; Nurhasanah, Iis Ariska (MDP Student Conference, 2025)
Fintech, or financial technology, has grown rapidly and is now a way to help micro-enterprises gain more access to capital. The purpose of this study is to examine how fintech can help Wonder Craft, a micro-enterprise in Pesawaran specializing in innovative knitting and beading, create an inclusive economy. This study uses a case study methodology combined with qualitative descriptive methods. In-depth interviews, observations, and documentation were used to collect data. The study findings show that fintech benefits micro-enterprises by making funding more accessible, increasing the effectiveness of digital transactions, and improving technology-based marketing. Wonder Craft was able to increase revenue, attract a wider audience, and strengthen local communities by leveraging fintech. This study shows that in the digital era, fintech plays a vital role in building a fair economic ecosystem for MSMEs.